2015
DOI: 10.1371/journal.pone.0142725
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dynamic Neonatal Blood-Brain Barrier on a Chip

Abstract: Studies of neonatal neural pathologies and development of appropriate therapeutics are hampered by a lack of relevant in vitro models of neonatal blood-brain barrier (BBB). To establish such a model, we have developed a novel blood-brain barrier on a chip (B3C) that comprises a tissue compartment and vascular channels placed side-by-side mimicking the three-dimensional morphology, size and flow characteristics of microvessels in vivo. Rat brain endothelial cells (RBEC) isolated from neonatal rats were seeded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
136
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 47 publications
8
136
1
Order By: Relevance
“…Briefly in this model, endothelial cells are seeded in the outer compartments, while astrocytes (BBB) or brain seeding breast cancer cells (BTB) are seeded in the central compartment. The porous architecture between the two compartments allows for cellular crosstalk and biochemical exchanges, while shear stress from perfusate flow facilitates development of endothelial morphology [19]. Confocal brightfield images show the differences in morphology between endothelial cells with and without flow (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly in this model, endothelial cells are seeded in the outer compartments, while astrocytes (BBB) or brain seeding breast cancer cells (BTB) are seeded in the central compartment. The porous architecture between the two compartments allows for cellular crosstalk and biochemical exchanges, while shear stress from perfusate flow facilitates development of endothelial morphology [19]. Confocal brightfield images show the differences in morphology between endothelial cells with and without flow (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, because the cells are grown in a static media, there is no shear stress (or flow) forced on the endothelial cells, which may contribute to the low passive permeability measurements which can be as low as ~74 Ω cm 2 [47], compared to in vivo values of ~2000 Ω cm 2 [48]. While a few other in vitro models and microfluidic devices have a flow component [2731], this microfluidic device is the first commercially available blood-tumor barrier using a microfluidic model seeded with brain-seeking cells and with shear stress similar to that observed in vivo [19] in addition to real-time visualization and quantitation.…”
Section: Discussionmentioning
confidence: 99%
“…39 Deosarkar et al also showed that endothelial cells exhibited tight junction formation, as measured by the expression of ZO-1 in microfluidic BBB models, and allowed endfeet-like neonatal astrocyte-endothelial cell interactions through a porous interface. 59 Although beyond the scope of this review, we note that microfluidic tissue chips have been applied toward a number of organ systems. 18,19,60 As a result, the microfluidic-based tissue chip design is commonly referred to as an organ-on-a-chip; however, we caution the reader that the ‘organ-on-a-chip’ concept does not strictly apply to microfluidic designs as alternative design and manufacturing approaches now exist for constructing tissue chips ( e.g.…”
Section: Classes Of Neural Systems On a Chipmentioning
confidence: 99%
“…[94] In two subsequent studies, Prabhakarpandian and Deosarkar et al reconstituted a BBB-on-chip constructed of two-compartments chamber with a microvascular channels cultured with rat brain endothelial cells under shear flow and a tissue compartment seeded with rat astrocytes under static flow as a 3D in vitro model to study neonatal neural pathology (Figure 4C). [95,96] Overall, current in vitro BBB models could not yet be fully applied to assess the mechanism pathways underlying human brain diseases. However, they are increasingly useful for assessing the toxicity of drugs for neurological diseases, together with in vitro 2D and in vivo models.…”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%